Kelimpahan dan Keanekaragam Tanaman Pakan Rusa Bawean di Kawasan Suaka Margasatwa Pulau Bawean, Jawa Timur - Subeno Subeno (Jurnal Ilmu Kehutanan, 2009)
Abundance and Diversity of Bawean Deer Foods in Bawean Wildlife Sanctuary,Bawean Island,East JavaBawean deer (Axis kuhlii) is an endemic species to Bawean. Habitat change and loss, land conversion, and over exploitation affect the availability of potential food forBawean deer. The aims of this research were to identifi  types ofpotential food for Bawean deer in Bawean Wildlife Sanctuary, the abundance ofpotential foods in Bawean Wildlife Sanctuary and the diversity of such potential foods. Data collected using line transects whose length was adjusted according to field condition. The line transects were located in parallel to natural trail of study area. Observation was done in the plots established along transect, where plant being eaten by Bawean deer was found. Plot has a circular form with diameter of 3.14 m. Distance between plots was determined to be 100 m. Indicators used to collect data were feces, footprint and bite or chew mark on food plants. Identification ofplant species was conducted directly for every plant which showed bite or chew mark Data concerning type ofplant and its number, part of plants which was bitten or chewed and plant height were recorded. Abundance will be determined from the number of potential foods in each location. The results were afterwards compared among three forest regions. The diversity of food plant species was determined using Shannon index. The result showed that there are 29 plants considered as potential food for Bawean deer. Most of the plants are grasses, and herbs, while woody plants are found in a small number. Leaves, shoots (buds) and fruits are part of plant often being eaten. There are 14 food plants occurred in Gunung Mas forest region, 27 food plants were found in Gunung Besar forest region and 13 food plants in Tanjung Cina Island. Taliata, rumput padang and gadung have high abundance in Gunung Mas forest region, the smallest abundance was occupied by kayu flat. Kabek-kabekan putih, lading-ladingan and taliata showed the highest abundance in Gunung Besar forest region, while karangsang has the lowest abundance. In Tanjung Cina Island, high abundance was dominated by gadung, taliowar and lading-ladingan. On the other hand, talicacing, kayu tekek and rombok putih showed low abundance. Among three study areas, Gunung Besar forest region has the highest diversity index, followed by Gunung Mas forest region and then Tanjung Cina Island.